Effect of planting time and spacing on yield, yield-attributing characters and ascorbic acid content of king chilli (Capsicum chinense) under polyhouse condition (Current Horticulture, 2024)
An experiment was conducted to find out the optimum time of planting and plant density on chilli in polyhouse at Department of Horticulture, CAU, Imphal, during rabi season of 2014-15. Four planting times viz. 30 November, 19 December, 7 January and 26 January were considered as factor A and three spacings, viz. 60 cm × 60 cm, 60 cm × 45 cm and 45 cm × 45 cm were considered as factor B. The experiment was laid out in FRBD (Factorial Randomized Block Design) with 3 replications. The highest number of fruits/plant (67.83), fruit yield/plant [fresh (279.00 g) and dry (71.77g)] and fruit yield/ha [fresh (13.78 t/ha) and dry (3.44 t/ha)] were exhibited when seedling were transplanted on 7 January at a spacing of 45 cm × 45 cm ((D1S3). Similarly, maximum fruit length (5.77 cm) and diameter (2.57 cm) were shown when planting was done on 26 January at a spacing of 60 cm × 45 cm (D4S2). Highest individual fruit weight (6.07 g) was achieved when planting was done on 7 January at a spacing of 60 cm × 60 cm (D3S2). Highest ascorbic acid (149 mg/g) content was obtained from the treatment D3S2 which was planted on done 7 January at a spacing of 60 cm × 45 cm.
Keywords: Ascorbic acid; Planting time; Poly-house; Spacing; Yield